Ajuste de un modelo matemático de adsorción/ desorción de un inhibidor de escamas inorgánicas (2019)
During the oil production phase, mineral compounds or crystals can precipitate in both the pores of the vicinity of the well and the pipes due to thermodynamic changes that occur by the extraction of hydrocarbons over time. Such a phenomenon is known as inorganic scales. This problem costs billions of dollars a year to the industry. Therefore, in the fields where this problem is present, the use of inhibiting agents that mitigate the formation and subsequent deposition of the scale is required. When carrying out a scale inhibition treatment, it is expected that the injected inhibitor be able to prevent the formation of such scales while remaining attached to the porous surfaces. Such treatments must be repeated periodically, which increases the lifting cost in those fields. The purpose of this work is to adjust the mathematical description of the adsorption/desorption phenomenon in order to improve both the treatment designs and the simulation times. Our work finishes mentioning that factors such as formation water pH, compatibility of injected fluids with reservoir fluid and the minimum inhibitor concentration are the elements to take into account with the reservoir properties as Temperature and Pressure are key points in the adjustment because they are the influential factors in the time in which the inhibitor will remain in the reservoir avoiding the presence of the scale.